Quantitative carbon ion beam radiography and tomography with a flat-panel detector - Telsemeyer, Julia; Jäkel, Oliver; Martišíková, Mária (Physics in medicine and biology, 2012)
High dose gradients are inherent to ion beam therapy. This results in high sensitivity to discrepancies between planned and delivered dose distributions. Therefore an accurate knowledge of the ion stopping power of the traversed tissue is critical. One proposed method to ensure high quality dose deposition is to measure the stopping power by ion radiography. Although the idea of imaging with highly energetic ions is more than forty years old, there is a lack of simple detectors suitable for this purpose. In this study the performance of an amorphous silicon flat-panel detector, originally designed for photon imaging, was investigated for quantitative carbon ion radiography and tomography. The flat-panel detector was exploited to measure the water equivalent thickness (WET) and water equivalent path length (WEPL) of a phantom at the Heidelberg Ion-Beam Therapy Center (HIT). To do so, the ambiguous correlation of detector signal to particle energy was overcome by active or passive variation of carbon ion beam energy and measurement of the signal-to-beam energy correlation. The active method enables one to determine the WET of the imaged object with an uncertainty of 0.5 mm WET. For tomographic WEPL measurements the passive method was exploited resulting in an accuracy of 0.01 WEPL. The developed imaging technique presents a method to measure the two-dimensional maps of WET and WEPL of phantoms with a simple and commercially available detector. High spatial resolution of 0.8 × 0.8 mm 2 is given by the detector design. In the future this powerful tool will be used to evaluate the performance of the treatment planning algorithm by studying WET uncertainties.